Substitusi Ubi Jalar Kuning dan Penambahan Ekstrak Daun â€œGondaâ€ (Spenochlea zeylanica Gaertner) pada Mie Basah - Dewa Made Hardi Juliana; Luh Suriati; I Putu Candra (Fakultas Pertanian, Universitas Warmadewa, 2019)
Noodle is a popular food and a favorite of all people. This is stimulated by consumers' need for nutritious, healthy, safe food and practical lifestyle. Noodles that currently exist predominantly contain carbohydrates derived from wheat flour. Substitution and the addition of other components to the noodles will provide added value so that it is more functional. This study aims to determine the effect of yellow sweet potato substitution and the addition of